1. OVERVIEW OF THE CURRENT SITUATION TO EFFECTIVELY APPLY THE WORLD HEALTH ORGANIZATION'S UPDATED RECOMMENDATIONS ON TREATMENT FOR DRUG-RESISTANT TUBERCULOSIS IN VIETNAM AND SOLUTIONS IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Based on recommendations of the World Health Organization (WHO) and assessment of the current situation in Vietnam; solutions are proposed to apply new treatment regimens for drug-resistant tuberculosis patients in Vietnam safely and effectively.Methods: Literature review from international and Vietnamese official websites, along with data and report from Vietnam National Tuberculosis Program.Result: Inadequate access to drug susceptibility testing (DST) for second-line anti-tuberculosis drugs has been recognized due to limited resources, sample transportation systems and laboratory supply chains. Monitoring bacteriological response during treatment is still limited due to difficulties affecting patient compliance. Treatment monitoring and drug safety management have shortcomings due to lack of resources and decentralization to peripheral level.Conclusion: Recommendations for Vietnam to invest resources to improve accessibility to DST and patient support to apply new regimens for drug-resistant tuberculosis patients safely and effectively.
Keywords: Drug-resistant tuberculosis, new regimen, BPaL(M), drug susceptibility testing, adverse events.